Endoscopic endonasal intraconal orbit surgery - Catherine Banks (KeAi Communications Co., Ltd., 2020)
Endoscopic endonasal orbital surgery is evolving. With increasing knowledge, expertise, and technology, the historical limits of the endonasal endoscopic approach to the orbit have been redefined. This review discusses the clinical presentation and etiology, and highlights the pertinent anatomy, and discusses the diagnostic workup and surgical approach to orbital tumors and post-operative care. The role of the multidisciplinary team is not to be underestimated. The introduction of a classification system to ensure standardization of technical difficulty and outcome data will assist with international collaboration and further consolidate our attainment of knowledge in this developing field.